Analysis of Translation Techniques of Directive Speech Acts in WALL-E Film - Bathara, Galih Wisnu; Noverino, Romel (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
The problem in this study relates to the study of translation, specifically on translation techniques which govern the way directive speech act is translated from English into Indonesian. This study aims to find out translation techniques of directive speech acts using Yule's theory (1996) and Molina and Albir's theory. The data sources of this study are WALL-E film and its Indonesian subtitles on a streaming platform Disney+ Hotstar. Based on the results, there are 81 data of directive speech, divided into Command with 20 data, Order with 41 data, Request with 11 data, and Suggestion with 9 data. The researcher also found 14 translation techniques which are used when translating English directive speech act into Indonesian from the sources of data, namely: amplification, borrowing, calque, compensation, discursive creation, established equivalent, generalization, linguistic amplification, linguistic compression, literal translation, modulation, particularization, reduction, and transposition. There were 37 data using single technique, 31 data using couplet technique, 11 data using triplet technique, and 2 data using quartet technique.